Optimum soil conditioning for Celosia Argentea propagation subjected to irrigation scheduling (2008)
Celosia argentea was planted on Agricultural and Environmental Engineering Department experimental field. The field was divided into nine plots of three different soil nutrient conditions (organic, inorganic, and control), labelled A1, A2, A3; B1, B2, B3; C1, C2, C3, respectively Plant growth parameters were measured and analyzed weekly starting from the third Week After Planting (WAP) to the sixth WAP when the crop was harvested. Growth parameters included height, stern girth, leaf area, and number of leaves. Maximum crop evapotranspiration rate based on Penman Montieth evapotranspiration equation were obtained using a CROPWAT 4 Windows Version 4.3 Software and subsequently, the irrigation amount required per day was determined. Measured data were analyzed statistically using the Generalized Linear Model (GLM) option of the Statistical Analysis System (SAS), Version 7.03. The results are presented in tables while the Duncan Multiple Range Test (DMRT) was used to separate the means based on their significant differences in order to determine the effects of variable water application rates and different nutrient conditions on growth parameters. It was concluded that Celosia argentea thrives better on soil with high content of organic matter, which retained more water than the inorganic soil nutrient condition and the control with no soil conditioning. Hence, under high economic pressure due to high poverty level in developing countries, application of organic fertilizer which is relatively cheaper than the inorganic chemical fertilizer can help maximize production with positive net returns and reduce environmental pollution from organic wastes produced mainly from agricultural industry